2022
DOI: 10.1002/vnl.21895
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the physical properties of acrylic resilient denture liner using graphene oxide nanosheets

Abstract: Resilient denture liners (RDLs) change their hardness in a short time. Hence, their usefulness is limited to the short term only. Therefore, this laboratory study investigated the influence of graphene oxide (GO) nanosheets incorporation on the longevity of a commercially available RDL material. An autopolymerizing acrylic-based RDL was selected for this purpose. The control group (G 0 ) was prepared as such according to the manufacturer's instructions.However, for the G 1 group, 0.1 wt/wt% of GO nanosheet was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Table 2 shows detailed information regarding the included studies. The studies included in this review evaluated polymers used in dentistry as Polymethylmethacrylate (PMMA) [20] , [21] , [22] , [23] , [24] , [38] , [39] , [40] , [41] and Poly-ether-ether-ketone (PEEK) [11] , [12] incorporated with graphene oxide (GO), [20] , [21] , [22] , [23] , [24] , [39] , [40] , [41] reduced graphene oxide (rGO) [38] and graphene nanoplatelets (GNP) [11] , [12] in concentrations ranging from 0.1 to 10 wt%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows detailed information regarding the included studies. The studies included in this review evaluated polymers used in dentistry as Polymethylmethacrylate (PMMA) [20] , [21] , [22] , [23] , [24] , [38] , [39] , [40] , [41] and Poly-ether-ether-ketone (PEEK) [11] , [12] incorporated with graphene oxide (GO), [20] , [21] , [22] , [23] , [24] , [39] , [40] , [41] reduced graphene oxide (rGO) [38] and graphene nanoplatelets (GNP) [11] , [12] in concentrations ranging from 0.1 to 10 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that incorporated graphene compounds into dental polymers to positively alter their mechanical properties [11] , [12] , [20] , [21] , [22] , [23] , [24] , [38] , [39] , [40] , [41] observed that, depending on the concentration and method of incorporation, these properties are negatively affected. [11] , [21] , [38] , [41] Thus, due to the versatility and graphene potential application in dentistry, this review evaluated which graphene compounds incorporated into dental polymers provide the increase in mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…One of the common drawbacks of soft denture liners is water sorption and solubility, and it was found that soft linings exhibited high solubility in artificial saliva [23]. This issue is correlated with the changes in the structure, physical properties [52], and the dimensional stability of the materials that may cause swelling, distortion, change in color, increased Candida albicans growth, and reduced bond strength by causing tensions at the liner denture base interface [50].…”
Section: Discussionmentioning
confidence: 99%
“…It facilitates cell adhesion, proliferation, and differentiation, thereby contributing to the regeneration of bone tissue. Meanwhile, the incorporation of GO into bone graft materials can enhance their mechanical strength and stability 24,25 . In addition, Kolanthai et al 26 found that the addition of GO could enhance the cross‐linking between the polymer matrix and the filler to increase the mechanical strength after γ‐ray radiation.…”
Section: Introductionmentioning
confidence: 99%